A Short Note on the Epitaph of Ama Helenê Ioudaia - Horst, Pieter Willem van der (Journal for the study of Judaism in the Persian, Hellenistic, and Roman period, 2017)
This short note proposes a new interpretation of the epitaph of Ama Helenê Ioudaia, an inscription recently published by L. H. Blumell in jsj 47 (2016): 310-29, on the basis of a different reading of some of the Greek words in this inscription.